Chemically reactive hybrid nanofluid flow past a Riga plate with nonlinear thermal radiation and a variable heat source/sink - Algehyne, Ebrahem A.; Lone, Showkat Ahmad; Raizah, Zehba; Eldin, Sayed M.; Saeed, Anwar; Galal, Ahmed M. (Frontiers in Materials, 2023)
The suspension of nanoparticles in base liquids has found extensive applications in various industrial processes like nanomedicines, microsystem cooling, and energy conversion. Owing to its important applications, this article investigates the hybrid nanofluid flow over a three-dimensional stretching surface. The fluid is influenced by thermal radiation, chemical reaction, and a variable thermal source/sink. The set of equations that administer the fluid behavior has been transformed to dimensionless form by a suitable set of similarity transformations that are further solved by the homotopy analysis method. It was found that as the ratio parameter increased, the velocity of hybrid nanofluid velocity decreased along the primary direction and increased along the secondary direction. The temperature characteristic was augmented with greater values of nonlinear thermal radiation and source/sink factors. Growth in the chemically reactive factor and Schmidt number has an adverse effect on the concentration profile of the hybrid nanofluid flow. A comparative analysis of the current results and those established in the literature was conducted. A close agreement with those published results was found. It was noted that temperature and concentration increase more quickly for the MoS2+MgO/H2O hybrid nanofluid than the MoS2/H2O,MgO/H2O nanofluids.